How UK PhD programs have prepared international students for work: perspectives of Chinese doctoral students in the social sciences - Zhao, Xin; Kung, Michael; Bista , Krishna (Journal of International Students, 2023)
International doctoral students are an indispensable part of the increasingly globalised Higher Education Institutions and play a vital role in continually refreshing the host country’s research base and fostering cross-national research collaborations. Despite their contributions, most international student employability experiences have been centred on undergraduate and master’s students, and fewer studies have been undertaken to explore the employability experiences of those who study for a doctoral degree. The research team conducted two focus groups with Chinese international doctoral students studying social sciences at two British universities. The focus groups examined the students’ perceptions of their employability development within the PhD programs and identified areas for enhancing international doctoral student employability. Results highlight an urgent need for UK universities to develop effective channels to support Chinese doctoral student employability, focusing on supervisors as career mentors, developing graduate skills through fieldwork and teaching opportunities, and co-publications.